Effect of Supplementation of Tulsi (Ocimum sanctum) Leaf and Ginger (Zingiber officinale) Powder as Feed Additive on Daily Weight Gain, Comparative Economics and Mortality Percent of Broiler Chicks - Shende, K. A.; Dhuria, R. K.; Goklaney, D.; Barolia, Y. K. (International Journal of Bio-resource and Stress Management, 2021)
A study was undertaken to evaluate the effect of tulsi and ginger as feed additives on comparative economics of broiler chicks. Two hundred and ten day-old chicks divided into 7 groups and each group having 30 chicks. Control group was fed on basal diet and T1 and T2 group were supplemented with 0.5% and 1% of tulsi leaf powder in the ration, respectively. Likewise, G1 and G2 group were supplemented with 0.5% and 1% of ginger powder in the ration, respectively. T1G1 and T2G2 treatment groups were supplemented with 0.5% and 1% of both herbs in combination, respectively. The statistical analysis of data revealed highly significant (p<0.01) effect of tulsi leaf and ginger powder on average daily body weight gain. Highest average daily body weight gain during starter phase was recorded in T2G2 group fed with tulsi leaf and ginger powder @ 0.5% each, which was comparable with G2 group. During finisher phase of trial statistical analysis revealed highest (p<0.01) average daily body weight gain in T2G2 group. Lowest average daily body weight gain was observed in control group during starter and finisher period. Statistical analysis of data revealed highly significant (p<0.01) effect on comparative economics of broilers due to supplementation of tulsi leaf and ginger powder. Highest net profit per kg of live weight was observed in T2G2 group supplemented with 0.5% tulsi leaf and ginger powder each and lowest net profit per kg of live weight was observed in T2 group which was comparable with control group. The overall mortality per cent of chicks under different treatment groups was observed to be 16.17% in control group and 6.66% in T1 and T2, and in G1, G2, T1G1, T2G2 groups observed no mortality. It may be concluded that supplementation tulsi leaf and ginger powder as feed additives improves daily weight gain, comparative economics and reduced mortality of broiler chicks.